0.06(y-4)+0.12y=0.20y-0.3

Simple and best practice solution for 0.06(y-4)+0.12y=0.20y-0.3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.06(y-4)+0.12y=0.20y-0.3 equation:


Simplifying
0.06(y + -4) + 0.12y = 0.20y + -0.3

Reorder the terms:
0.06(-4 + y) + 0.12y = 0.20y + -0.3
(-4 * 0.06 + y * 0.06) + 0.12y = 0.20y + -0.3
(-0.24 + 0.06y) + 0.12y = 0.20y + -0.3

Combine like terms: 0.06y + 0.12y = 0.18y
-0.24 + 0.18y = 0.20y + -0.3

Reorder the terms:
-0.24 + 0.18y = -0.3 + 0.20y

Solving
-0.24 + 0.18y = -0.3 + 0.20y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-0.20y' to each side of the equation.
-0.24 + 0.18y + -0.20y = -0.3 + 0.20y + -0.20y

Combine like terms: 0.18y + -0.20y = -0.02y
-0.24 + -0.02y = -0.3 + 0.20y + -0.20y

Combine like terms: 0.20y + -0.20y = 0.00
-0.24 + -0.02y = -0.3 + 0.00
-0.24 + -0.02y = -0.3

Add '0.24' to each side of the equation.
-0.24 + 0.24 + -0.02y = -0.3 + 0.24

Combine like terms: -0.24 + 0.24 = 0.00
0.00 + -0.02y = -0.3 + 0.24
-0.02y = -0.3 + 0.24

Combine like terms: -0.3 + 0.24 = -0.06
-0.02y = -0.06

Divide each side by '-0.02'.
y = 3

Simplifying
y = 3

See similar equations:

| -28+15-22z=3131 | | p+5=52 | | 6r+8s-7s-r+3r= | | 5n+-9n=-16 | | 12-3x^2=23x | | U=F(a+R) | | x-7.5=2x | | f(x)=2pi*x | | R=.66t+v | | 1.4z+2.2=2.7z-0.2 | | 5.4t+14.6-10.1t=.4(25+j) | | 5a+15b=-24 | | 4(8-5)=152 | | f(x)=13x+9 | | 7(x+2)+1=15-7x | | V-80=5 | | 2x-7y+11x-4y= | | -14=7y+64 | | 2x-4(x-3)=-4+3x-24 | | 96-u=68 | | 4t-7=4t-7 | | -2v^2-v+12=-3v^3+6v | | a-5+8=5 | | 5c-6=3c-8 | | 3(y-2)-7=12-2y+6 | | 6x+2y=42 | | 92+s=98 | | 2236000-17740x=45 | | 18+32=p-32 | | 15=21x+36 | | 2(3x-3)=(4x-2) | | (3n)(4n)= |

Equations solver categories